2021
DOI: 10.3390/ma14206042
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electrical Properties of the Al/SiO2/n++-Si Resistive Switching Structures by Means of Static, Admittance, and Impedance Spectroscopy Measurements

Abstract: In this study, the resistive switching phenomenon in Al/SiO2/n++-Si structures is observed and studied by means of DC, small-signal admittance, and complex impedance spectroscopy measurements. Possible transport mechanisms in the high and low resistance states are identified. Based on the results of the applied measurement techniques, an electrical equivalent circuit of the structure is proposed. We discuss the effect of parasitic elements influencing the measurement results and show that a proper model can gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…However, in order for preserving the switching layer quality relatively more vulnerable in the LRS state and device reliability over the long-time frequency sweep period under a DC bias stress, the value was lowered to 0.7 V for the measurement in the LRS. Once the bias voltage is lower than the set voltage (~ 3.8 V in this work), it was experimentally confirmed that there was no significant change in impedance analysis results with a change in bias voltage in performing the frequency sweep [ 44 ]. As the frequency goes higher, the trajectory is plotted in the counterclockwise direction.…”
Section: Resultsmentioning
confidence: 76%
“…However, in order for preserving the switching layer quality relatively more vulnerable in the LRS state and device reliability over the long-time frequency sweep period under a DC bias stress, the value was lowered to 0.7 V for the measurement in the LRS. Once the bias voltage is lower than the set voltage (~ 3.8 V in this work), it was experimentally confirmed that there was no significant change in impedance analysis results with a change in bias voltage in performing the frequency sweep [ 44 ]. As the frequency goes higher, the trajectory is plotted in the counterclockwise direction.…”
Section: Resultsmentioning
confidence: 76%
“…Between the HRS and LRS, memristors can, in general, possess resistive, capacitive and inductive properties to some degree [18]. Specifically, this resistive and capacitive behavior is observed in the HRS while some inductive characteristics are displayed in the LRS [19,20]. Therefore, when studying such devices, it is opportune to apply a characterization technique capable of isolating and measuring all three of these properties.…”
Section: Introductionmentioning
confidence: 99%
“…EIS has been used in the past to study mostly non-volatile memristors, for example, ones with switching layers of TiO x [18,19,[25][26][27][28][29], SiO x [19,28,30], Cu/SiO 2 [28], HfO 2 [27], WO x [22], Ge 2 Sb 2 Te 5 [31] and Ag/Si [32]; both in the HRS and LRS. The only comparable example of an EIS study on a volatile memristor that we are aware of was [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some works have presented research on SiO 2 as a promising material for those devices [ 17 , 18 , 19 , 20 ]. In our recent works, we showed that well-known silicon oxide in a materials stack of Al/SiO 2 /n++-Si can also exhibit resistive switching properties [ 21 , 22 ]. However, little work relates to the effect of temperature on the device’s performance [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%